The Relation between Immunological Features and the Positive SARS-CoV-2 Nucleic Acid in Patients with Nonsevere COVID⁃19. (30th July 2022) - Zhang, Dong; Li, Xueren; Sun, Haibai; Shi, Lixia; Peng, Shouchun
Abstract : Objective . The novel coronavirus nucleic acid results are the core indicators of illness monitoring. This study aimed to evaluate the relationship between immunological features and positive SARS-CoV-2 nucleic acid by analyzing the clinical and immunological features in nonsevere COVID-19 cases. Methods . Data from nonsevere COVID-19 patients admitted to Haihe Hospital from May 2020 to June 2021 were retrospectively reviewed and analyzed. Results . (1) A total of 122 cases were reviewed in the present study, including 38 mild and 84 moderate cases. The average age of mild cases was significantly different from moderate cases (P < 0.001 ). Eight patients complained of hyposmia and it was more frequent in mild cases (P < 0.001 ). The nucleic acid positive duration (NPD) of nonsevere novel coronavirus was 20.49 (confidence interval (CI) 17.50–3.49) days. (2) The levels of specific IgM and IgG for COVID-19 were higher in mild cases than in moderate cases (P = 0.023 and P = 0.047, respectively). (3) The correlation analysis with antibodies and T-cell subtypes showed that the lymphocyte (LYM) count, T cells, CD4 + T cells, and CD8 + T cells had a linear correlation with NPD. (4) Among the 93 patients monitored, 62 COVID-19 cases presented a progressive rise of specific IgM and IgG. The daily increase rates of IgM and IgG were 38.42% (CI 28.22–48.61%) and 24.90% (CI 0.23–29.58%), respectively. Conclusion . The levels and daily increase rates of specific IgM and IgG against the virus can vary between cases. The NPD presented a linear correlation with the LYM, T cells, CD4 + T cells, and CD8+T cells. Hence, more attention should be paid to these indicators in clinical practice.